The role of multi-scale modeling in assessing livelihood adaptation strategies to climate change - Herrero, Mario; Thornton, Philip K. (La Goliardica Pavese s.r.l., 2007)
The Earth’s climate is changing at unprecedented rates, largely due to anthropogenic factors (IPCC 2007). This, together with other drivers such as population increases and increased demand for crop and livestock products, is causing agro-ecosystems to evolve faster than previously expected. These changes will have profound impacts on land use, global food security, energy use, the economics of agricultural systems and their sustainability, and the livelihoods of rural populations. Inevitably, the associated uncertainty of the magnitude and timing of these effects will make farming decisions more riskier and difficult. Climate change adaptation strategies will need to be developed, particularly in situations where vulnerability is high. The role of integrated models at different scales (regions and households) is likely to become more prominent as scenarios and solutions need to be devised and downscaled to be useful to relevant stakeholders. This paper outlines the climate change impacts and the effects of other drivers of change on agricultural systems and the livelihoods of farmers dependent on them. We continue with a description of existing models operating at different scales (from downscaled global circulation models to household models) and suggest ways in which they can be used to assess different adaptation strategies to cope with climate change impacts. We illustrate these concepts with case studies from highly vulnerable regions, mainly in smallholder systems in Africa.